2005
DOI: 10.1128/jb.187.13.4521-4530.2005
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Nicotinamide Mononucleotide Requires Periplasmic AphA Phosphatase inSalmonella enterica

Abstract: Salmonella enterica can obtain pyridine from exogenous nicotinamide mononucleotide (NMN) by three routes. In route 1, nicotinamide is removed from NMN in the periplasm and enters the cell as the free base. In route 2, described here, phosphate is removed from NMN in the periplasm by acid phosphatase (AphA), and the produced nicotinamide ribonucleoside (NmR) enters the cell via the PnuC transporter. Internal NmR is then converted back to NMN by the NmR kinase activity of NadR. Route 3 is seen only in pnuC* tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 51 publications
0
61
0
Order By: Relevance
“…NR is one of several related compounds (vitamers) that have been named vitamin B3 and is a precursor of the cofactor NAD (Figure 1), which is found in all living organisms. The specificity of PnuC for NR has been demonstrated for homologs from Escherichia coli (Sauer et al, 2004), Haemophilus influenzae (Kemmer et al, 2001), Haemophilus parainfluenzae (Cynamon et al, 1988), S. typhimurium (Grose et al, 2005b), and Neisseria mucosa (Jaehme et al, 2014). In contrast to other Pnu homologs, the genomic organization of the genes encoding PnuC is not well conserved.…”
Section: Tracking Pnu Transporter Homologsmentioning
confidence: 98%
See 4 more Smart Citations
“…NR is one of several related compounds (vitamers) that have been named vitamin B3 and is a precursor of the cofactor NAD (Figure 1), which is found in all living organisms. The specificity of PnuC for NR has been demonstrated for homologs from Escherichia coli (Sauer et al, 2004), Haemophilus influenzae (Kemmer et al, 2001), Haemophilus parainfluenzae (Cynamon et al, 1988), S. typhimurium (Grose et al, 2005b), and Neisseria mucosa (Jaehme et al, 2014). In contrast to other Pnu homologs, the genomic organization of the genes encoding PnuC is not well conserved.…”
Section: Tracking Pnu Transporter Homologsmentioning
confidence: 98%
“…However, subsequent research showed that both transporters are similar and also use a similar mode of transport. In both organisms, periplasmic machineries have been identified that breakdown NAD and NMN to NR, which is the transported substrate of PnuC (Cynamon et al, 1988;Kemmer et al, 2001;Herbert et al, 2003;Sauer et al, 2004;Grose et al, 2005b). Shortly after cloning of PnuC, it became evident that its activity strongly depends on the regulator NadR (Foster et al, 1987(Foster et al, , 1990Zhu et al, 1989.…”
Section: A General Scheme For Pnu Transportermediated Uptakementioning
confidence: 99%
See 3 more Smart Citations